Desenvolvimento de biscoito tipo cookie isento de glúten - Fernandes, Angélica Maria Delovo (2017)
Celiac Disease is an autoimmune disease that affects individuals with genetic predisposition, and prevents them from ingesting foods with gluten, a protein found in many cereals, especially wheat. But gluten is a substance that offers specific characteristics to the pasta. The objective of this work was to develop a gluten-free cookie-type food. This work presents the elaboration of nine gluten-free cookie formulations, which were carried out through an experimental design. From a standard formulation with rice flour, other formulations were proposed using sorghum flour, teff flour and rice flour, differing only the percentages of the flour used. These formulations were analyzed sensorially by fifty tasters, through a hedonic scale of 9 points, where 9 corresponded to the most highly liked and 1 corresponded to the most disagreeable, being evaluated the attributes color, flavor, texture and overall impression. The attributes color, flavor, texture and overall impression differed significantly between samples (p <0.05), since the odor attribute did not differ between samples. Even though the samples differed from each other, the overall impression averages ranged from only 6.84 to 7.82. Another parameter analyzed in the sensory analysis was the intention to buy, through a scale of 5 points where 1 corresponds to certainly buy, and 5 corresponds to certainly not buy. The same presented satisfactory results where the scores were lower than 2.5. From the analysis results, an optimized cookie was formulated with the cross-referencing of fiber content, cost and purchase intention information. The proposed formulation was 40% rice flour, 35% sorghum flour and 25% teff flour, with high fiber content, and acceptable cost.